The concept of race in South Asia - Robb,Peter (Editor) (SOAS studies on South Asia : understandings and perspectives series, 1995)
South Asia has always played a part in the European imagining of race, but has not been considered in the scholarly literature of the present generation; nor, recently, have concepts of race figured very prominently in South Asian Studies. This volume constitutes one of the first attempts to raise the question comparatively and over a long time-span with regard to South Asia.